Pulsed ultraviolet light for microbial inactivation and its applications for food decontamination - Uslu-Senel, Gulsad; Demirci, Ali (Elsevier, 2023)
Pulsed light is a nonthermal technology that utilizes the germicidal effect of light against bacteria, viruses, and fungi. It could serve as an alternative to current antimicrobial interventions in the food industry. The generation of UV, UV-LED, and pulsed light is obtained from different sources. Light-based technology is an alternative to thermal and chemical decontamination methods as it results in minimal influence on the food quality attributes. In recent years, light technology using UV has found more applications in the food production chain as it is an economical, effective, and versatile dry processing technology. This chapter provides an overview of UV systems, their applications in solid and liquid foods, and their efficacy in microbial inactivation. © 2024 Elsevier Inc. All rights reserved.
Keywords: food decontamination; low-pressure mercury; microbial inactivation; nonthermal technology; Pulsed ultraviolet light